Arsenic exposure and lung fibrotic changes-evidence from a longitudinal cohort study and experimental models - Wang, Chih-Wen; Chiou, Hsin-Ying Clair; Chen, Szu-Chia; Wu, Da-Wei; Lin, Hung-Hsun; Chen, Huang-Chi; Liao, Wei-Ting; Lin, Ming-Hong; Hung, Chih-Hsing; Kuo, Chao-Hung (Frontiers in Immunology, 2023)
Introduction: Arsenic (As) exposure is associated with lung toxicity and we aim to investigate the effects of arsenic exposure on lung fibrotic changes. Methods: Participants (n= 976) enrolled from general health survey underwent chest low-dose computed tomography (LDCT), spirometry forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and urinary arsenic examination during 2016 and 2018. Lung fibrotic changes from LDCT was defined. AsLtoL, low arsenic levels in both 2016 and 2018; AsLtoH, low arsenic in 2016 but high levels in 2018; AsHtoL, high arsenic in 2016 but low levels in 2018; AsHtoH, high arsenic levels in both 2016 and 2018. Mice exposed to 0. 0.2mg/L, 2 mg/L, 50 mg/L of sodium arsenite (NaAsO2) through drinking water for 12 weeks and 24 weeks were applied for histological analysis. Cultured lung epithelial cells were exposed to NaAsO2 and the mesenchymal changes were examined. Results: AsHtoH increased the risk (OR= 1.65, 95% CI 1.10, 2.49) of Lung fibrotic positive to positive (reference: Lung fibrotic negative to negative) compared with AsLtoL. Moreover, the predicted mean of FVC and FEV1 in AsHtoH (−0.09 units, 95% CI: −0.27, −0.09; −0.09 units, 95% CI: −0.17, −0.01) and AsLtoH (−0.13 units, 95% CI: −0.30, −0.10; −0.13 units, 95% CI: −0.22, −0.04) was significantly lower than ASLtoL. Significant lung fibrotic changes including the increase of the alveolar septum thickness and collagen fiber deposition were observed upon 2 mg/L NaAsO2 treatment for 12 weeks, and the damages were dose-and time-dependent. In vitro, sodium arsenite treatment promotes the epithelial-mesenchymal transition (EMT)-like changes of the normal human bronchial epithelial cells, including upregulation of several fibrotic and mesenchymal markers (fibronectin, MMP-2, and Snail) and cell migration. Inhibition of reactive oxygen species (ROS) and MMP-2 impaired the arsenic-induced EMT changes. Administration of a flavonoid, apigenin, inhibited EMT in vitro and pulmonary damages in vivo with the reduction of mesenchymal markers. Discussion: we demonstrated that continued exposure to arsenic causes lung fibrosis in human and mice. Targeting lung epithelial cells EMT is effective on the development of therapeutic strategy. Apigenin is effective in the inhibition of arsenic-induced pulmonary fibrosis and EMT.